Parotid Incidentaloma Identified by Positron Emission/Computed Tomography: When to Consider Diagnoses Other than Warthin Tumor - Bothe, Carolina; Fernandez, Alejandro; Garcia, Jacinto; Lopez, Montserrat; León, Xavier; Quer, Miquel; Lop, Joan (International Archives of Otorhinolaryngology, 2015)
Introduction Parotid gland incidentalomas (PGIs) are unexpected hypermetabolic foci in the parotid region that can be found when scanning with whole-body positron emission/computed tomography (PET/CT). These deposits are most commonly due to benign lesions such as Warthin tumor.Objective The aim of this study was to determine the prevalence of PGIs identified in PET/CT scans and to assess the role of smoking in their etiology.Methods We retrospectively reviewed all PET/CT scans performed at our center in search of PGIs and identified smoking status and standardized uptake value (SUVmax) in each case. We also analyzed the database of parotidectomies performed in our department in the previous 10 years and focused on the pathologic diagnosis and the presence or absence of smoking in each case.Results Sixteen cases of PGIs were found in 4,250 PET/CT scans, accounting for 0.4%. The average SUVmax was 6.5 (range 2.8 to 16). Cytology was performed in five patients; it was benign in four cases and inconclusive in one case. Thirteen patients had a history of smoking. Of the parotidectomies performed in our center with a diagnosis of Warthin tumor, we identified a history of smoking in 93.8% of those patients.Conclusions The prevalence of PGIs on PET/CT was similar to that reported by other authors. Warthin tumor is frequently diagnosed among PGIs on PET/CT, and it has a strong relationship with smoking. We suggest that a diagnosis other than Warthin tumor should be considered for PGIs in nonsmokers.
Keywords: parotid gland; adenolymphoma; PET scan; cigarette smoking